Hubungan Perilaku Picky Eater dengan Kecukupan Zat Gizi Makro dan Status Gizi Anak Usia Prasekolah di TK Lab School 1 Unesa - Khofifah Dewi; Amalia Ruhana (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Picky eating behavior is a common feeding problem among preschool-aged children. Children who exhibit picky eating tendencies often reject various types of food, especially new or unfamiliar ones, placing them at risk of an imbalanced intake of macronutrients such as energy, protein, fat, and carbohydrates. Inadequate nutritional intake over the long term may negatively impact a child's nutritional status and growth. This study aims to examine the relationship between picky eating behavior and the adequacy of macronutrient intake including energy, protein, fat, and carbohydrates and nutritional status among preschool children at Lab School 1 Kindergarten, State University of Surabaya. This research utilized a quantitative design with a cross-sectional approach. The study population consisted of 60 preschool children aged 4–6 years (48–73 months), selected using total sampling. After applying inclusion and exclusion criteria, a total of 37 respondents were included. Data were collected using the Child Eating Behavior Questionnaire (CEBQ) to assess picky eating behavior, interviews with the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to evaluate macronutrient intake, and anthropometric measurements to determine nutritional status. Data analysis was conducted using the Spearman Rank correlation test. The results showed a significant relationship between picky eating behavior and energy intake (p=0.002; r=0.495), fat intake (p=0.002; r=0.502), carbohydrate intake (p=0.006; r=0.443), and nutritional status (p=0.002; r=-0.493) among preschool children at Lab School 1 Unesa. However, no significant relationship was found between picky eating behavior and protein intake (p=0.064; r=0.307).